Comparison of Path Planning Algorithms for an Unmanned Aerial Vehicle Deployment Under Threats. Issue 13 (2019) - Danancier, Kevin; Ruvio, Delphine; Sung, Inkyung; Nielsen, Peter
Abstract: Following the massive interests in unmanned aerial vehicles (UAVs), various optimization algorithms have been proposed for a path planning problem that allow the units to navigate in a region filled with threats such as a radar detection in air defence systems. Among the algorithms, we address Dijkstra's algorithm and a heuristic algorithm for the path planning of a UAV. The algorithms are compared under various configurations of a region to navigate with respect to the optimality and the computational complexity of the algorithms.